Adherence to nutritional guidelines in pregnancy: evidence from the Growing Up in New Zealand birth cohort study. Issue 9 (9th April 2014) - Morton, Susan MB; Grant, Cameron C; Wall, Clare R; Carr, Polly E Atatoan; Bandara, Dinusha K; Schmidt, Johanna M; Ivory, Vivienne; Inskip, Hazel M; Camargo, Carlos A
Abstract Objective To determine adherence to nutritional guidelines by pregnant women in New Zealand and maternal characteristics associated with adherence. Design A cohort of the pregnant women enrolled into New Zealand's new birth cohort study, Growing Up in New Zealand. Setting Women residing within a North Island region of New Zealand, where one-third of the national population lives. Subjects Pregnant women (n 5664) were interviewed during 2009–2010. An FFQ was administered during the face-to-face interview. Results The recommended daily number of servings of vegetables and fruit (≥6) were met by 25 % of the women; of breads and cereals (≥6) by 26 %; of milk and milk products (≥3) by 58 %; and of lean meat, meat alternatives and eggs (≥2) by 21 %. One in four women did not meet the recommendations for any food group. Only 3 % met all four food group recommendations. Although adherence to recommendation for the vegetables/fruit group did not vary by ethnicity (P=0·38), it did vary for the breads/cereals, milk/milk products and meat/eggs groups (all P<0·001). Adherence to recommendations for the vegetables/fruit group was higher among older women (P=0·001); for the breads/cereals group was higher for women with previous children (P<0·001) and from lower-income households (P<0·001); and for the meat/eggs group was higher for women with previous children (P=0·003) and from lower-income households (P=0·004). Conclusions Most pregnant women in New Zealand do not adhere to nutritional guidelines in pregnancy, with only 3 % meeting the recommendations for all four food groups. Adherence varies more so with ethnicity than with other sociodemographic characteristics.